The issue of two women in the korean art world - SAIDAZIMOVA, UMIDA TURAKHANOVNA (The journal of contemporary issues in business and government, 2021)
Without a woman, there would be no literature. Literature was created primarily for a woman, for a woman, to win her heart, to know what she wants, to understand what a woman is. As Abdullah Qahhor said, the male bird also sings. Word art is, first of all, the work of a man, so the main problem that interests a person will be the main problem of literature. Therefore, the main character of literature, the main theme is a woman[1].